Regulasi Pembayaran Pajak Penghasilan Untuk Warga Negara Yang Pergi Keluar Negeri - Maura Faradita; Mhd Khairul Anhar Nasution; Mhd Aldi Pratama (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
This journal discusses a review of previous research on the income tax payments for citizens traveling abroad. This payment is in the form of prepayment of income tax and can be accessed by individuals who are more than 21 years old with appropriate income. The main focus of this study is to analyze the prevailing tax regulations in Indonesia and international tax treaties. This journal is a literacy that aims to understand the procedures for tax payment, payment exemptions, and management of income tax administration for domestic individual taxpayers who will travel abroad.